Strategi Manajemen Konten Dakwah Digital dalam Menjangkau Generasi Milenial - Karina Sofiananda Armaza Faraba; Fathurrohman, Mukhlis; Safitri, Desi Ana (Faculty of Cultural Studies, Universitas Brawijaya, 2025)
The focus of this service activity is to contribute to the implementation of da'wah management strategies. The outreach activity to the community is carried out to provide an understanding of digital da'wah content management strategies, especially for the millennial generation. The introduction of digital da'wah content for the millennial generation aims to increase knowledge and literacy that da'wah activities in the current era can be implemented through digital media. The community service activity was held on February 15, 2025 at TPQ Al-Hikmah Plosorejo, Empuh Village, Andong District, Boyolali Regency. The number of participants in the activity consisted of 5 village officials, 5 village youth coaches, 35 village youth (gamapro youth organization), 20 PKK women, and 25 PKN IIM Surakarta students. In this activity, the assisted participants were given explanations and examples of digital da'wah content management strategies. All participants, especially village youth who are prioritized in the activity, have understood and made a design of a digital da'wah content management strategy.